A=U for Locally Acyclic Cluster Algebras - Muller, G. (Symmetry, Integrability and Geometry: Methods and Applications, 2014)
This note presents a self-contained proof that acyclic and locally acyclic cluster algebras coincide with their upper cluster algebras.